THE RELATIONSHIP BETWEEN THE LEVEL OF KNOWLEDGE OF CONTACT LENS WEAR WITH THE INCIDENCE OF EYE IRRITATION IN UMI MEDICAL FACULTY STUDENTS - Fadya, Atiqa; Maharani, Ratih Natasha; Iskandar, Darariani; Kusumawardhani, Sri Irmandha; Aulia, Nur (HEARTY, 2025)
Contact lens wear is increasing every year, a large part of which is to help those with nearsightedness or myopia. There are 140 million people in the world who use contact lenses and two-thirds of them are women. Objective: to determine the characteristics (age and gender) of students who wear contact lenses with the Faculty of Medicine UMI class of 2022-2023. To determine the description of knowledge (uses, types of fluids, and usage patterns) of contact lens wear with the incidence of eye irritation in students / female students of the Faculty of Medicine UMI class 2022-2023. To determine the frequency of eye irritation in students / (i) Faculty of Medicine UMI class of 2022-2023. To determine whether there is a relationship between the level of knowledge of contact lens use and the incidence of eye irritation in students / (i) Faculty of Medicine UMI class 2022-2023. As well as to find out the purpose of wearing contact lenses, types of contact lenses and how to wear contact lenses on students (i) Faculty of Medicine UMI class 2022-2023. Methods: The research design used in this study was descriptive analytic research with a cross-sectional design. Results: The majority of respondents were 20 years old, from the class of 2022, and female. Of the 110 respondents, the majority (74.5%) had sufficient knowledge and did not experience eye irritation, while only 10.0% with less knowledge experienced irritation. Respondents with good knowledge (8.2%) all did not experience irritation. The knowledge level of contact lens use was mostly in the moderate category, and most respondents did not experience eye irritation. Statistical tests showed a negative correlation (-0.582, sig. = 0.000) between the level of knowledge and the incidence of eye infections, where the higher the knowledge, the lower the incidence of eye infections. The majority of respondents used contact lenses as a visual aid, with a duration of wear of more than one year, a type of contact lens that can be used repeatedly, and a daily duration of wear of more than 6 hours.Conclusion: The majority of respondents had a moderate level of knowledge about contact lens use and did not experience eye irritation. There was a significant negative relationship between the level of knowledge and the incidence of eye infections, where the higher the knowledge, the lower the risk of infection. Respondents generally used contact lenses as a visual aid with a long duration of wear.